Effect of Blood sugar, temperature and time on blood alcohol levels in Autopsy blood samples (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
The effects of blood sugar, temperature and time on blood alcohol concentration in 60 autopsy blood samples were studied. Femoral blood samples were collected which were divided into twp groups (A and B). Group A samples were stored at –20 0C and Group B samples were stored at room temperature for 60 days. The mean blood sugar of all the samples was 275.81+ 26.3 mg%. The mean baseline Blood alcohol concentration (BAC) was 39+ 5mg%. Samples stored at –20 0 C showed insignificant rise in BAC i.e. 44.6 + 4mg% and 52.75 +6mg% after 15 and 60 days respectively. Group B showed significant rise in BAC i.e. 84.5 + 3 mg% and 118.6 + 5mg% after 15 and 60 days respectively. Samples with higher blood sugar levels i.e. > 140mg% had higher BAC in both Group A and B, as compared to blood sugar levels < 140mg%.
Keywords: Alcohol; Postmortem generation; Blood sugar; Temperature